Pathogen and host factors are needed to provoke a systemic host response to gastrointestinal infection of Drosophila larvae by Candida albicans. - Glittenberg, M; Kounatidis, I; Christensen, D; Kostov, M; Kimber, S; Roberts, I; Ligoxygakis, P (2011)
Candida albicans systemic dissemination in immunocompromised patients is thought to develop from initial gastrointestinal (GI) colonisation. It is unclear what components of the innate immune system are necessary for preventing C. albicans dissemination from the GI tract, but studies in mice have indicated that both neutropenia and GI mucosal damage are crucial for allowing widespread invasive C. albicans disease. Mouse models, however, provide limited applicability to genome-wide screens for pathogen or host factors - factors that might influence systemic dissemination following GI colonisation. For this reason we developed a Drosophila model to study intestinal infection by Candida. We found that commensal flora aided host survival following GI infection. Candida provoked extensive JNK-mediated death of gut cells and induced antimicrobial peptide expression in the fat body. From the side of the host, nitric oxide and blood cells influenced systemic antimicrobial responses. The secretion of SAP4 and SAP6 (secreted aspartyl proteases) from Candida was also essential for activating systemic Toll-dependent immunity.